Stakeholder management: evidence on the performance of publicly traded companies - Cintra, Renato Fabiano; Ribeiro, Ivano; Fava, Helder de Lima; Costa, Benny Kramer (Revista de Administração da UFSM, 2023)
Purpose: This study consists of empirical evidence from stakeholder management in the performance indicators of publicly traded companies. Design/methodology/approach: The methodological framework was quantitative, and the Mann-Whitney U test was used in order to make comparisons between groups (with/without stakeholder management). Findings: As a result, there is the empirical evidence of stakeholder management in the discussion of value creation and organizational performance. Research implications: This study advances in the empirical discussion of the relationship between stakeholders and the company in the orientation of value creation, since it provides statistical evidence that the stakeholder management has influence on the performance of companies. Research limitations: As a limitation, the study has the composition of the sectors, which can be expanded in future research, for all sectors of the BM&F Bovespa, including the 362 companies. A sample with several sectors can improve the inferences. Practical implications: The study improves the understanding that it is not the fact that it belongs to the index, as it is the case of ISE-GRI, that the company’s results point to a superior performance of those that do not belong, but the effective management of stakeholders for a positive result in the short and long term, as it was evidenced in this study. Originality/value: It also demonstrates the empirical evidence of issues, until then dealt with in the theoretical field, but with no direct relationship with a set of companies, as well as supporting the idea that the creation of connections between companies and stakeholders open invisible opportunities for value creation.